ANALISIS FLYPAPER EFFECT PADA DANA ALOKASI UMUM DAN PENDAPATAN ASLI DAERAH TERHADAP BELANJA DAERAH DI INDONESIA - Dwi Pratiwi; RASTRI PARAMITHA (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2016)
In 1999, the Government of Indonesia introduced local autonomy to the level of regional governance. It coerces a regional government to be ready to accept more responsibility in governing and managing its house affairs. The main funding sources of local governments come from Own-Source Revenue (PAD). Besides, they also get help from central government transfer such as Balancing Funds (Dana Perimbangan) Which Consist of General Allocation Funds (DAU), Specific Allocation Funds (DAK) And Revenue Sharing Funds (DBH). The regional transfer funds aim to provoke the local government to generate more their own revenue. The regions however become more dependent on central government. Instead of optimizing their own sources income, they tend to enjoy the transfer funds from the central government. There is an indication of asymmetric behavior in response to the transfer of local government. It implies that the regional transfer (i.e. general allocation fund) increases the level of public spending more than an increase in local income of an equivalent size. This study has the objective to provide empirical evidence for the occurrence of flypaper effect on government spending in Indonesia. The study is using a multiple regression as method analysis. This study result indicates that there is flypaper effect on DAU in Indonesia.